PELAKSANAAN PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) DI KOTA PEKANBARU - Afriansyah "; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Pekanbaru City is one of the cities with a high level of urbanization. Therefore, conflicts and land problems often occur, due to unclear land ownership in the community. To overcome these problems the Government issued a Systematic Complete Land Registration Program (PTSL) is a step forward in facilitating the management of land certificates. The aim of this researcher is to find out the implementation of a Systematic Complete Land Registration (PTSL) in Pekanbaru City. The focus of research on the theory of Implementation by Repley and Franklin in (Tahir, 2015) which states there are three indicators, namely: bureaucratic compliance levels, smooth routines and no problems, and performance. The results of the study showed that the implementation of the Systematic Complete Land Registration Program (PTSL) in Pekanbaru City was not optimal because of the slow performance of the implementor in the management of land certificates. The inhibiting factors were the human resource factor and the time limitation factor. Keywords: Policy, Implementation of Policy, Land Policy